Insurreição na garganta: a estética-política em Elza Soares - Moreli, Lígia Moreira (2021)
This dissertation examines the artist Elza Soares (Rio de Janeiro, RJ, 1930), and seeks to investigate her transition towards an aesthetics-politics, her insurgent traits and the transversality of her music post-digital social networks. The research corpus focuses on the effects of her 2015 album A Mulher do Fim do Mundo [The Woman at the End of the World], correlated to her concert at the 2019 Rock in Rio festival and its impact on social networks, particularly on Instagram. The research is aimed at pointing out the poetics of insurgency, latent throughout the artist's trajectory and revealed in all its power in the album A Mulher do Fim do Mundo, which we define here as a political-aesthetic postulate. To achieve this, we explore the performatic components and the political meaning of Elza Soares’s artistic and innovative statements in the 21st century, including such songs as “A Mulher do Fim do Mundo,” “Maria da Vila Matilde” [Maria from Vila Matilde], “Benedita,” and the revival of the iconic “A Carne” [The Meat], as well as declarations by the artist against racism, misogyny and homophobia. The instrumental of interpretation employed in this research is based on Christine Mello's extremities approach, which relies on the notions of deconstruction, contamination and sharing to explore the limits between social spaces, artistic actions, and mediatic languages. Drawing on this interpretation we will reflect on the dimension of the insurgency in the poetics of Elza Soares and how it problematizes the tensions between the global and the peripheral world, shedding light on the subjectivities of the so-called minority groups as a possibility for micropolitical resistance to advance a debate on and the possibility of a new world. The interdisciplinary theoretical structure encompasses the fields of philosophy, with an emphasis on contemporary aesthetics (Jacques Rancière), black feminism (Lélia Gonzalez) and the emergence of the struggles of Afro-diasporic bodies (Leda Maria Martins); political sciences and psychoanalysis, with investigations on micropolitics and post-colonialism (Suely Rolnik); and media theories addressing image, aesthetics, and biopolitics of the feminine (Tarcisio Torres Silva)